2013
DOI: 10.1016/j.pocean.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the distribution of a threatened albatross: The importance of competition, fisheries and annual variability

Abstract: a b s t r a c tThe ability to predict the distribution of threatened marine predators is essential to inform spatially explicit seascape management. We tracked 99 individual black-browed albatrosses Thalassarche melanophris from two Falkland Islands' colonies in 2 years. We modeled the observed distribution of foraging activity taking environmental variables, fisheries activity (derived from vessel monitoring system data), accessibility to feeding grounds and intra-specific competition into account. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 45 publications
3
45
0
Order By: Relevance
“…For the main fish species (those contributing >10% of amplified sequences), the depth profile for each species during different age stages were compiled from the literature to determine which were likely to be naturally accessible to albatrosses (Table S1 in Supplementary Material). This study focused on the fishing zones adjacent to the breeding sites, as these are likely to be used more intensively than distant waters by foraging birds during chick-rearing (Phillips et al, 2004;Terauds et al, 2006;Catry et al, 2013;Arata et al, 2014), and secondly, the management of these areas is within the same national jurisdiction as the relevant breeding site. However, we acknowledge that birds may have also interacted with fisheries further from colonies, especially during incubation when BBA are foraging farther from the colony than during chick rearing (Phillips et al, 2004;Wakefield et al, 2011) …”
Section: Assessing Overlaps Between Commercial Fisheries and Bba Preymentioning
confidence: 99%
“…For the main fish species (those contributing >10% of amplified sequences), the depth profile for each species during different age stages were compiled from the literature to determine which were likely to be naturally accessible to albatrosses (Table S1 in Supplementary Material). This study focused on the fishing zones adjacent to the breeding sites, as these are likely to be used more intensively than distant waters by foraging birds during chick-rearing (Phillips et al, 2004;Terauds et al, 2006;Catry et al, 2013;Arata et al, 2014), and secondly, the management of these areas is within the same national jurisdiction as the relevant breeding site. However, we acknowledge that birds may have also interacted with fisheries further from colonies, especially during incubation when BBA are foraging farther from the colony than during chick rearing (Phillips et al, 2004;Wakefield et al, 2011) …”
Section: Assessing Overlaps Between Commercial Fisheries and Bba Preymentioning
confidence: 99%
“…Researchers have used these methods to address specific aspects of seabird distributional ecology such as habitat suitability (Ceia et al 2012;Oppel et al 2012;Catry et al 2013;Louzao et al 2013;McGowan et al 2013;Scales et al 2016), identification of hotspots in the present and past (Louzao et al 2013), selection of potential conservation areas and potential climate change impacts (Krüger 2017). But, many of the more recent applications use ensemble modelling (Scales et al 2016;Krüger 2017) or incorporate seabird movement data (Clay 2016;Quillfeldt 2017) that, whilst increasing in quantity and availability, is nowhere near as prevalent or accessible as point observation data.…”
Section: Discussionmentioning
confidence: 99%
“…Improved correlative modelling approaches, building on the baseline presented herein, can significantly enhance understanding of macroscale factors driving distributional dynamics of species, including pelagic seabirds and other highly mobile species, and provide crucial information to fill important information gaps necessary to project and explore the future distributional potential (Louzao et al 2011;Catry et al 2013). These insights, in combination with increasing knowledge of species' natural history and ecology, can inform conservation planners and offer information vital to the research priorities identified by Lewison et al (2012) including identification and mapping of movement corridors and foraging areas to understand impacts of global change on the distributions of pelagic seabirds and other highly mobile species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as it was previously stated, the overlapping between ice trawlers and BBas strongly suggests that the contribution of demersal fish to the diet of these birds during winter comes from the ice-trawl fleet. However, given the similitude between ice and freezer trawlers in the target species and by-products of the fishing operation, we understand that freezer trawlers should be regarded in the same way for conservation and management purposes, at least during moments of the annual cycle when BBas are distributed further south in the vicinity of breeding grounds (granadeiro et al 2011;Catry et al 2013). available information shows that the trawler fleet from Uruguay has the argentine hake as one of main target species (99.8 % of total landing for this species, DInara 2010) and this species is also discarded by shrimp-trawl fleet operating further south at the argentinean Continental Shelf, hence suggesting that BBas could be making use of discards from these fleets as well.…”
Section: Discussionmentioning
confidence: 99%